Crenarchaeol tracks winter blooms of ammonia‐oxidizing Thaumarchaeota in the coastal North Sea - Angela Pitcher; Cornelia Wuchter; Kathi Siedenberg; Stefan Schouten; Jaap S. Sinninghe Damsté (Limnology and Oceanography, 2011)
We followed the abundance and distribution of ammonia‐oxidizing Archaea (AOA) in the North Sea from April 2003 to February 2005 and from October 2007 to March 2008 by quantification of archaeal genes and core glycerol dibiphytanyl glycerol tetraether (GDGT) membrane lipids in suspended particulate matter, to determine whether their abundance in the North Sea is seasonal. GDGT and gene abundance increased during winters and was low during the summer. Crenarchaeol—a GDGT specific to AOA—was a major fraction of the GDGTs and varied in concert with AOA gene abundance, indicating that AOA are the predominant source of crenarchaeol. The presence of crenarchaeol‐based intact polar lipids (IPLs) confirmed that the GDGTs recovered were derived from living AOA, as IPLs are rapidly degraded upon cell senescence and thus their occurrence represents living biomass more robustly than their fossil (i.e., core GDGT) counterparts. Dark incubations of North Sea water sampled during the 2007–2008 seasonal cycle with 13 C‐labeled bicarbonate revealed incorporation of inorganic carbon into IPL‐derived GDGTs, directly showing autotrophic production of Thaumarchaeota biomass during the winter. Inhibition of 13 C uptake by nitrification inhibitors confirmed that ammonia oxidation was the main source of energy for carbon fixation. Winter blooms of planktonic AOA in the North Sea were recurrent and predictable, occurring annually between November and February, emphasizing the potential importance of AOA in nitrogen cycling in the North Sea.

Proteomic analysis of secreted membrane vesicles of archaeal Sulfolobus species reveals the presence of endosome sorting complex components - Albert F. Ellen; Sonja-Verena Albers; Wim Huibers; Angela Pitcher; Cedric F. V. Hobel; Heinz Schwarz; Mihaela Folea; Stefan Schouten; Egbert J. Boekema; Bert Poolman; Arnold J. M. Driessen (Extremophiles, 2009)